A standardized approach to test missense PNPLA1 rare genetic variants of uncertain significance in epidermal differentiation disorders - Pell, Nuria; Bernard, Pauline; Courrech, Séverine; Opalka, Lukas; Millán-Sánchez, Aina; Levy, Elise; Garnier, Séverine; Clément, Cyrielle; Le Faouder, Pauline; Vávrová, Katerina; López, Olga; Bertrand-Michel, Justine; et al. (JID innovations, 2026)
Congenital ichthyoses, now renamed epidermal differentiation disorders (EDDs) (syndromic EDD or nonsyndromic EDD), are rare, disabling conditions caused by sequence variations in epidermal barrier genes. However, 5-10% of variants, called "variants of uncertain significance" (VUS), remain uncharacterized, and their pathogenicity is not demonstrated. We developed an approach for classifying VUS in nonsyndromic EDD associated with variant in PNPLA1. We generated PNPLA1-knockout human keratinocytes. PNPLA1, encoded by a missense VUS or by the reference coding sequence, was expressed after lentiviral transduction in the PNPLA1-knockout cells. Transduced cells were used to produce human epidermal equivalents, and the functionality of the normal or VUS-encoded proteins was evaluated. Compared with PNPLA1-knockout human epidermal equivalents re-expressing normal PNPLA1, PNPLA1-knockout human epidermal equivalents showed disrupted synthesis of ω-O-acylceramide, the normal product of PNPLA1, as well as abnormal vesicle-like structures and immature cornified envelopes, characteristic of the epidermis of patients with PNPLA1 variants. Human epidermal equivalents expressing the PNPLA1 VUS showed similar abnormalities, consistent with an impaired PNPLA1 function. This work demonstrated a feasible strategy to help reclassifying missense VUS, which can be extended to other EDD-related genes. Although further efforts are needed to translate this approach into clinical practice and help overcome current diagnostic limitations, such models are valuable tools for pathophysiological and preclinical research on EDDs.
Keywords: Genodermatosis; Skin barrier; Ichthyosis; Human epidermal equivalents; Functional genetics